Power Quality Enhancement Using Renewable Energy Sources and Electric Mobility - Mohamed Khaleel (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
In the present day, there is a growing emergence of obstacles pertaining to the remuneration of power quality (PQ) issues. In this context, the implementation of renewable energy sources (RES) solutions has a critical significance. The transition from traditional electrical power grids to smart grids necessitates the utilization of a significant quantity of power electronics converters and RES. These converters are essential for the incorporation of crucial technologies like renewable energies, electric mobility, and energy storage systems. Consequently, PQ concerns gain heightened significance in this context. The article focuses on elucidating the primary phenomena related to PQ issues in smart grids, their origins, and consequences across various sectors. Additionally, the paper provides a comprehensive examination and categorization of the primary PQ issues, along with their corresponding alignment with established standards. It also offers an assessment of PQ problems associated with RES and their integration with electric mobility.